Eosinophil accumulation predicts response to melanoma treatment with immune checkpoint inhibitors - Simon, Sonja C. S.; Hu, Xiaoying; Panten, Jasper; Grees, Mareike; Renders, Simon; Thomas, Daniel; Bitsch, Rebekka; Schulze, Torsten J.; Utikal, Jochen; Umansky, Viktor (OncoImmunology, 2020)
Eosinophils have been identified as a prognostic marker in immunotherapy of melanoma and suggested to contribute to anti-tumor host defense. However, the influence of immune checkpoint inhibitors (ICI) on the eosinophil population is poorly studied. Here, we applied routine laboratory tests, multicolor flow cytometry, RNA microarray analysis, and bio-plex assay to analyze circulating eosinophils and related serum inflammatory factors in 32 patients treated with pembrolizumab or the combination of nivolumab and ipilimumab.
Gesehen am 02.04.2020